THE ROLE OF THE GOVERNMENT IN THE PROTECTION OF COMMUNITY LAND ON GREEN-ZONE - Dewi, Nourma (International Journal of Research -GRANTHAALAYAH, 2021)
Land rights are one of the rights of life of the community. This right should have been protected by the state as the implementation of Article 33 paragraph (3) of the 1945 Republic of Indonesia Constitution that the earth and natural wealth in it are protected by the state and used for the people’s prosperity. This right is violated by the determination of land owned by the people declared in the green zone so that its use and allocation is limited by the government. On the other hand, when the land will be used in the framework of government planning, the status of the land will change according to the interests of the government. This phenomenon illustrates that the law that should support the state to give a sense of justice to the people on the contrary makes people’s rights not fulfilled. The aim to be achieved in this study is to analyze the role of the government in protecting community land rights in the green zone. This research is normative legal research. Based on the research, it was concluded that community welfare and community justice were not well accommodated by the government regarding land in the green zone because there was a lack of clear arrangements regarding the ability to transfer the land.